Statement in regard to the Minister of Health's White Paper on the establishment of "A National Health Service." (1944)
1944 1944 1940s 18 pages We have already indicated our ppinion [opinion] that in the course of time the whole of the people's interest in these services may be taken over and controled [controlled] entirely by the medical heirarchy [hierarchy], It is for this reason that trade unionists of all kinds must take up the struggle to retrain [retain] whatever interests they have in the Health Services, and to extend such interest to the full. It is interesting to note in regard to the inspection of hospitals that "The foundation of any inspectorate must clearly be a team of highly qualified medical men."? As a kind of sop the report adds - "Hospital administrators, nurses, catering experts and others - should find a place." Let us hope that in the others a place will be found for the stoker and the domestic who know where to look for defects. Surely it is time the medical man were told to look after their own job - i.e. the medical side of a hospital. Those who have had experience of medical men as administrators or inspectors know that in 75 per cent they are hopeless failures. And yet - the inspectors of this new service are to be highly qualified medical men. The more qualified they are, the more up in the clouds they become. Are they to inspect the hospital solely to see that the plan is functioning properly. Are they to visit the hospital to ensure that the citizen is getting a proper deal; that the services are really efficient; and that the staff are happy and contented, and too, are receiving fair and just consideration. Will any of their reports be available for public inspection.? Will they be kept as ''Secret Dossiers" by the Minister.? The Trades Union Congress should insist that for each administrative Area a Trade Unionist shall be appointed as an Inspector as nominee of the movement, who will have the right of reporting to the General Council any defects in the system from all aspects, mainly in the interest of the public, patients and the staff. Further more we suggest that for each hospital there shall be set up a staff consultative committee consisting of elected representatives of the various grades of staff in the hospital, and that the inspector, whoever he may be, shall meet such committee on his visit and will consult them and receive from them any representations or suggestions for the interest of the hospital, such representatives to be reported to the Minister of Health. 14, STAFF PROBLEMS. In any such comprehensive Health Service the position of the staff should be clearly stated. We have previously dealt with the aspect as it affects the staff in regard to training and promotion; we have indicated the obscurity as to the body which is to be responsible for the continued employment of staff and regulation of conditions of such employment. One factor is clear and that is that the Voluntary Hospitals have a clear field. They continue as they are and benefit by and through exchequer grants. It is immaterial that the administrative costs of each voluntary hospital will continue, and possibly increase, particuarly [particularly] as greater scope for development arises. [P]robably at the expence of other municipal hospital services. Conditions governing the staff should be uniform, and such that will lead to mobility i.e. unrestricted transfer from one hospital to another. How is this to be done.? Again the Government mind is blank. Employees of Local Government Authorities have a statutory superannuation scheme operating, and in most instances there are regulations governing wages and conditions of employment. Mental Hospital employees have a seperate superannuation scheme, and wage rates and conditions are governed by a Joint Conciliation Committee. Voluntary Hospital employees have no statutory superannuation scheme, and wage rates and conditions are generaly [generally] on determinations of the B.H.A. How can mobility be ensured under such conditions.? What steps are to be taken to obtain uniformity, particulary [particularly] of superannuation rights,? Rushcliff[e] Committee are already dealing with this latter problem as far as it covers the nursing staff. But what of the thousands of other hospital employees who are not governed by Rushcliffe.? This can only be effectively carried out by the establishment of a Joint Consultative Committee, consisting of representatives of the Central controlling authority (if there is to be one) and the organised employees through their trade unions. 14. 292/847/2/43